Impact of MW rays on extraction and application of Ficus religiosa bark based natural colourant for cotton dyeing. (February 2022) - Akram, Waseem; Adeel, Shahid; Amin, Nimra; Habib, Noman; Inayat, Asma; Mirnezhad, Somayeh
The present study aims to extract a natural brown colourant from Ficus religiosa for cotton dyeing using the microwave radiation process. The colourant was isolated in aqueous and acidic media before and after microwave treatment (MW) for up to 6 min. The dye variables have been optimised for the development of new shades with good fastness characteristics, 1–5 g/100 mL of sustainable chemical and bio-mordants have been used. It has been found that irradiated aqueous extract (RE) containing 3 g/100 mL of salt at 55°C for 45 min has given high colour yield onto cotton fabric (RS) after microwave treatment for 4 min. The utilization of 2% of Al, 2% of Fe, 3% of tannic acid (T.A.) as pre chemical mordant whereas 4% of Al, 5% of Fe, 2% of tannic acid as post chemical mordant has given good colour characteristics. In comparison 3% of acacia and 4% pomegranate while 4% of Acacia and 2% of pomegranate extracts as post-bio-mordant have given excellent colour characteristics. It is concluded that MW treatment has an excellent sustainable efficacy to isolate colourant from Ficus Religiosa bark powder for cotton dyeing, whereas the inclusion of bio-mordants has made the process more sustainable and environmental friendly.